2019
DOI: 10.3390/ma12142311
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Osteogenic Differentiation of Mesenchymal Stem Cells by Bioceramic Root Repair Material

Abstract: This study aimed to evaluate the osteogenic activity of Endosequence Root Repair Material (ERRM) putty using rat mesenchymal stem cells (MSCs). The extract of set ERRM and ProRoot-mineral trioxide aggregate (MTA) (control) was cocultured with rat MSCs and incubated for one, three, and seven days. The cell viability and proliferation were assessed. A quantitative real-time polymerase chain reaction for bone morphogenetic protein-2 (BMP-2), alkaline phosphatase, bone sialoprotein, and osteocalcin gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…Zhang et al51 demonstrated in ADSC (adipose-derived mesenchymal stem cells) that ES activates the flow of calcium through voltage-dependent channels, stimulating osteogenesis.Both TNAP and BSP-II are involved in the mineralization, organization, and calcification of the bone matrix. A time-dependent increase in the activity of these proteins was observed in the repair of bone fractures [52][53][54]. The analyses for TNAP and BSP-II expression in our study highlighted that grafting with BB was efficient in with ES and EM in the last experimental period.…”
supporting
confidence: 54%
“…Zhang et al51 demonstrated in ADSC (adipose-derived mesenchymal stem cells) that ES activates the flow of calcium through voltage-dependent channels, stimulating osteogenesis.Both TNAP and BSP-II are involved in the mineralization, organization, and calcification of the bone matrix. A time-dependent increase in the activity of these proteins was observed in the repair of bone fractures [52][53][54]. The analyses for TNAP and BSP-II expression in our study highlighted that grafting with BB was efficient in with ES and EM in the last experimental period.…”
supporting
confidence: 54%
“…Mineral trioxide aggregate (MTA) was developed due to its tight sealing potential and favorable biological properties; it also has odontoblastic and cementoblastic properties [ 5 , 6 , 7 ]. Previous studies have demonstrated favorable clinical outcomes following direct pulp capping with MTA compared to calcium hydroxide [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A positive effect of MTA on viability of rat BMSCs is observed up to day 7, which is sooner than in human BMSCs. Simultaneously, MTA stimulates rat BMSC differentiation into osteoblast-like cells over 7 days, which is confirmed by enhanced ALP staining and upregulation of gene expression levels of bone morphogenetic protein 2 ( BMP-2), ALP , bone sialoprotein ( BSP ) and osteocalcin (OC ) ( 109 ). Low concentrations of MTA-conditioned media (2.000, 0.200, 0.020 and 0.002 mg/ml) are not toxic to BMSCs and 0.02 mg/ml MTA is the optimal concentration to upregulate odonto/osteogenic capacity of BMSCs originating from rat mandible; this finding was supported by enhanced Alp activity, calcified nodule formation and expression levels of odonto/osteoblastic genes in BMSCs, such as ALP, RUNX2, OSX, OCN and DSPP .…”
Section: Stem Cellsmentioning
confidence: 88%